PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI DI KANTOR CAMAT HILIMEGAI KABUPATEN NIAS SELATAN - Laia, Eligius; Waruwu, Yurmanius (Universitas Nias Raya, 2024)
The problem of this research is the atmosphere of employee workspaces that are still less efficient so that employees feel less comfortable in working, less available work facilities such as desks, computer machines so that it is less supportive of smoothness in completing office work, there are still employees who are less harmonious in communicating with colleagues so that it can affect decreased work motivation. The purpose of this study is to find out the influence of the work environment on the work motivation of employees in the Hilimegai Camat Office of South Nias Regency. The type of research used is a quantitative type of causal nature. The data source was from employees, with the population and sample in the study being as many as 30 people. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study show that the work environment (X) has a positive and significant effect on the. growth; celery.